Congenital Lumbar Hernia with Lumbocostovertebral Syndrome: A Case Report and Review of the Literature. (18th September 2013) - Vagholkar, Ketan; Dastoor, Khojasteh
Abstract : Introduction . Congenital lumbar hernia is one of the rare types of hernias. Anomalies of the ribs, spine, and muscles which constitute the lumbocostovertebral syndrome in association with congenital lumbar hernia make it the rarest of entities. In addition, a multitude of other organ systems may be involved. Case Report . A case of congenital lumbar hernia associated with lumbocostovertebral syndrome is presented in view of its rarity and diagnostic and therapeutic challenges. Discussion . Anatomical background of congenital lumbar hernia associated with various other anomalies especially of the musculoskeletal structures is discussed. All cases of congenital lumbar hernia should be investigated for other congenital anomalies. Both open and laparoscopic approaches have been described for surgical treatment. Conclusion . Open surgical intervention is the mainstay of treatment taking into consideration the technical challenges posed by distorted anatomy due to the associated congenital anomalies.